The Notion of Common and Social Representations - Denise Jodelet (Peoples' Friendship University of Russia (RUDN University), 2021)
The recent emergence of social and political movements calling for common sense and the use of the notion of common in philosophy and social sciences has led to the opening of a reflection on the social and scientific representations concerning them. After having mentioned some political uses of the notions of common sense and common, we examine a notion that is closely associated with them: that of community on which S. Moscovici expresses a reserved position but introduces a new perspective on cybercommunities and the importance attached to affectivity in community groups. The ways of dealing with common sense, identified over time, from antiquity to the present day, highlight certain recurrences from a double perspective. From a typological point of view, several characterizations are distinguished: through simple sharing, through the sameness of moral values and emotional dimensions, through rooting in daily experience, through its devaluation as a form of knowledge in relation to science, through rationality, through its potential for revolt or on the contrary through conformity. From a conceptual point of view, common sense is analyzed as an epistemic characteristic of a group, in its content, formation, transmission, and role in social cohesion. The latest developments in the reflection highlight its link with democracy and populism. The term common of recent appearance is situated opposite the notion of common goods which, after having focused on material realities, now integrates the facts and practices of knowledge, being the subject of a specific domain: the commons of knowledge. The common appears as a new way of approaching social relationships and responds to the desire to introduce a relational, ethical and political dimension into the analysis of social and change processes. In this respect, the call to the common presents affinities with the approach of social representations. The examination of the different scientific and secular representations regarding the notions of community, common sense and common makes it possible to establish connections with the perspective of the study of social representations and to open the way for new investigations.